2018
DOI: 10.1136/oemed-2017-104796
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects among workers exposed to multiwalled carbon nanotubes

Abstract: The associations between MWCNT exposure and ICAM-1 indicate endothelial activation and an increased inflammatory state in workers with MWCNT exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 39 publications
(33 reference statements)
2
22
0
Order By: Relevance
“…The idea that ENM may have a fibrogenic function in exposed workers may be confirmed by epidemiological findings of increased levels of pro-fibrotic markers in serum and sputum of MWCNT-handling workers (123,124) and by RNA transcriptional analysis (127). Various findings are highly suggestive of the potential for cardiovascular dysfunction resulting from a systemic inflammatory status following pulmonary exposure (89,90,112,117,124,125,146,166).…”
Section: Summary Of Data and Occupational Health Considerationsmentioning
confidence: 90%
See 1 more Smart Citation
“…The idea that ENM may have a fibrogenic function in exposed workers may be confirmed by epidemiological findings of increased levels of pro-fibrotic markers in serum and sputum of MWCNT-handling workers (123,124) and by RNA transcriptional analysis (127). Various findings are highly suggestive of the potential for cardiovascular dysfunction resulting from a systemic inflammatory status following pulmonary exposure (89,90,112,117,124,125,146,166).…”
Section: Summary Of Data and Occupational Health Considerationsmentioning
confidence: 90%
“…As regards cardiovascular adverse effects, a recent study (125) investigated the associations between MWCNT-exposure and biomarkers of cardiovascular risk. The authors found a significant dose-dependent upward trend in the concentration of endothelial damage marker ICAM-1 in 22 MWCNT-exposed workers, compared to age-/gender-matched unexposed controls (125). This may indicate a MWCNT-induced endothelial activation and an increased inflammatory state, which may be related to cardiovascular effects.…”
Section: Carbon Nanotubes and Carbon Nanofibersmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have attracted considerable attention as a polymer additive because of their unique electrical properties . However, discrete CNTs and bundles of CNTs are known to induce numerous toxicological and pathological effects in experimental animals and may induce alterations in respiratory and cardiovascular function in workers, though epidemiology studies are not consistent . This observed toxicity of native CNTs raises concern about the potential toxicity of inhaling polymer‐associated CNT particles .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, discrete CNTs and bundles of CNTs are known to induce numerous toxicological and pathological effects in experimental animals and may induce alterations in respiratory and cardiovascular function in workers, though epidemiology studies are not consistent. [13][14][15][16] This observed toxicity of native CNTs raises concern about the potential toxicity of inhaling polymer-associated CNT particles. 17 To date, most studies of CNT release from polymer composites have focused on low-energy processes (eg, environmental degradation from UV light) or high-energy processes (eg, drilling and sanding).…”
mentioning
confidence: 99%
“…ENMs may enter other human organs and generate toxicity after they are absorbed into the bloodstream through the respiratory systems (Mu et al 2014). As the persistence of inflammation and oxidative stress in the lungs may have a "systemic" impact on the body, other matrices could be relevant for assessing systemic inflammatory and oxidative stress response (Beard et al 2018;Kuijpers et al 2018;Schulte et al 2019). Blood usually represented an ideal matrix for many chemicals due to its interaction with the organism and its chemical equilibrium with organs and tissues.…”
Section: Introductionmentioning
confidence: 99%